Structural design and temperature control enabling high sensitivity nanomaterial-based three-electrode gas sensors - Muhammad Waqas; Yong Zhang; Saif Aldeen Saad Obayes Alkadhim; Xiaoyu Li; Liang Xie (Scientific Reports)
Abstract Ionization based gas sensors using nanomaterials hold significance in monitoring gases but often suffer from issues such as excessive positive ion bombardment, which reduces lifespan, current collection, and detection accuracy. This study introduces a two-dimensional plasma discharge current model based on particle mass conservation, electron energy conservation, and Poisson equations to evaluate the discharge characteristics and electric fields distribution effects on sensor performance across various morphologies and cathode nanomaterial quantities, with experimental validation. The results indicated that the diffusion aperture diameter structure adjustment in sensor electrode surface maintains a high reverse electric field E 1 around the nanotips of the cathode, accelerated maximum positive ions away from nanomaterial, which reduces positive ion bombardment. The novel Φ = 1.2 × 9 mm diffusion aperture sensor with a 150 nm gold nanostructured cathode effectively directed approximately ~ 2/3 of positive ions from the ionization to the collection region, mitigating corrosion and bombardment effects. Compared to previous structure, this novel sensor shows three times greater sensitivity to H2, C2H2, CH4, SO2, NO, and O2, with enhanced detection ranges down to ppm, ppb, and ppt levels.